Combustion of eucalyptus charcoals and coals of similar volatile yields aiming at blast furnace injection in a CO sub(2) mitigation environment - Pohlmanna, Juliana G; Borregob, Angeles G; Osorioa, Eduardo; Diezb, Maria Antonia; Vilelaa, Antonio CF (Journal of cleaner production, 2016)
Reduction of CO sub(2) emissions due to partial substitution of coal by a renewable fuel, like woody biomass, is a subject of increasing interest in the ironmaking process. Additionally, the combination of biomass combustion with CO sub(2) capture technologies, such as oxy-fuel, could allow a negative CO sub(2) balance for industrial processes. This study aims to investigate the combustibility of eucalyptus densified at different temperatures compared to coals of similar volatile matter contents typically used for Pulverized Coal Injection (PCI) in blast furnace. Combustion at different O sub(2)/N sub(2) (conventional combustion) and O sub(2)/CO sub(2) (oxy-fuel combustion) concentrations of pulverized samples was carried out in a Drop Tube Furnace (DTF) at 1300 degree C. The characteristics of the chars were evaluated by their reactivity to CO sub(2) in thermobalance, optical microscopy and adsorption isotherms techniques. The conversion of thermally-treated biomasses in the DTF was greater than that of the coals with similar volatile matter contents and combustion under oxy-fuel (O sub(2)/CO sub(2)) conditions appeared to be favored compared with conventional combustion (O sub(2)/N sub(2)) at the same oxygen concentration. The low volatile biomasses yielded isotropic char particles with cellular structure whereas the high volatile biomasses generated swollen particles with vacuolated cell walls which approach in appearance to those of low rank coal chars. The biomass yielded chars with higher micro- and mesopore surface areas than the coal chars of equivalent volatile yields, and greater surface areas at oxy-fuel conditions compared to conventional combustion chars. About 7-10% in average higher conversions were observed for the most reactive biomass and coal chars when combusted under oxy-fuel conditions in DTF. The higher combustibility and reactivity of biomass-chars compared to coal-chars in both O sub(2)/N sub(2) and O sub(2)/CO sub(2) environments could be positive to its incorporation in PCI providing a high reactivity fuel whose volatile matter could be adjusted depending on the needs to maintain the volatile stability in the blast furnace.